ANALISIS STRATEGI UMKM JASA MINDFULNESS TRAINING (Studi Pada Bali Usada Health Meditation) - Amanda, Ayulia; Supriono, Supriono (Jurnal Administrasi Bisnis, 2019)
This research uses descriptive research with a qualitative approach. The author interviewed with the general manager, secretary, and instructor to find out the strategies that had been implemented. Interviews were also conducted with several students and alumni of Bali Usada Health Meditation to find out an overview of the motivations, experiences, and benefits they had felt during or after attending a meditation training program. The results of the study related to the analysis of the SWOT strategy, it was found that Bali Usada Health Meditation had major strengths in the brand and the founder as the main guru. The main weaknesses of this business are the limited human, marketing and financial resources. Opportunities that need to be maximized are competitive advantages, openness with cooperation, and meditation training programs for children and adolescents. Bali Usada Health Meditation does not feel threatened by the emergence of new meditation training businesses in Bali and Jakarta. Government support in the form of regulation is needed because it can advance the meditation subsector and tourism in Indonesia. There are several new strategies mapped in the form of a SWOT matrix in this study. Keywords: Meditation, SWOT, Wellness Industry. ?BSTR?K Penelitian ini menggunakan jenis penelitian deskriptif dengan pendekatan kualitatif. Penulis melakukan wawancara dengan general manager, sekretaris, dan instruktur untuk mengetahui strategi yang telah diterapkan. Wawancara juga dilakukan dengan beberapa murid dan alumni Bali Usada Health Meditation untuk mengetahui gambaran motivasi, pengalaman, dan manfaat yang telah mereka rasakan saat atau setelah mengikuti program pelatihan meditasi. Hasil penelitian terkait analisis strategi SWOT, ditemukan bahwa Bali Usada Health Meditation memiliki kekuatan utama pada merek dan pendiri selaku guru utama. Kelemahan bisnis ini yang utama ada pada terbatasnya sumber daya manusia, pemasaran, dan keuangan. Peluang-peluang yang perlu dimaksimalkan adalah keunggulan kompetitif, keterbukaan dengan kerjasama, dan program pelatihan meditasi untuk anak dan remaja. Bali Usada Health Meditation tidak merasa terancam dengan kemunculan bisnis-bisnis pelatihan meditasi baru di Bali dan Jakarta. Dukungan pemerintah dalam bentuk regulasi sangat dibutuhkan karena dapat memajukan subsektor meditasi dan pariwisata Indonesia. Ada beberapa strategi baru yang dipetakan dalam bentuk matriks SWOT pada penelitian ini. K?t? Kunci: Meditasi, SWOT, Wellness Industry.